TRAINING IN CASSAVA PROCESSING TECHNOLOGY INTO VARIOUS FUNCTIONAL FOODS - Asmawati; Dina Soes Putri; Syirril Ihromi; Arman Maulana; Siti Nurazizah; Meli Apriana; Hana Nita Isnaini (STKIP Citra Bakti, 2024)
Cassava is a local commodity that can be processed into functional food. Functional food is defined as a food or drink that provides nutrients for the body while simultaneously maintaining a healthy body. Although there has been a long tradition of processing cassava into traditional snacks, the decreasing interest of consumers, especially young people, in traditional snacks makes it necessary to innovate products. For instance, the processing of cassava into contemporary products such as nuggets, sponge cake, and tapai drinks. The objective of this community service activity is to educate partners regarding the necessity of consuming functional food, particularly from local commodities such as cassava, and to instruct partners on the processing of cassava, which is abundant in their area, into various functional food products with commercial value. The partners of this activity were members of the West Lombok 'Aisyiyyah Regional Leadership (PDA), a total of 16 women. The service activity is divided into three sessions: functional food counselling, cassava processing practice, and practice using sealers to package products. Prior to and following the activity, participants were administered a test to assess the impact of the service activity on their knowledge and skills in processing functional food and packaging products. The results of the pre- and post-test data processing indicate that there have been significant changes (32.5% improvement) in the participants' knowledge. Furthermore, the results of the observations of the participants' practical activities demonstrate that all participants have been able to process cassava into a variety of contemporary functional food products with a selling value and have become proficient in using cup and hand sealers.